A new opera house: combining entrepreneurship, garbage can features and windows of opportunity. (December 2015) - Christensen, Tom
This study looks at the decision-making that culminated in the building of a new opera house in Oslo. The decision was finally taken in 1999 and the new opera house was finished in 2008. To analyse the decision-making process we use a 'revised garbage can model', as presented by Kingdon, which combines the concept of political entrepreneurship through instrumental coalition-building with garbage can features. The winning coalition included actors from parliament and local government but also local private business interests, and it succeeded because it managed to capitalize on a window of opportunity opened by other actors. The main reasons for this were that the opera project was temporarily decoupled from a large road-building project and managed to bring on board interests connected to a more extensive city development in Oslo's inner east city. The relative weakness of the cultural arguments for building an new opera house were evident during the whole process, making the decision to build it a side effect or spin-off from other concerns and interests. The study, which is a single embedded case, is based on a wide range of public documents, interviews and newspaper articles. Points for practitioners: Decisions on major public projects may not follow a strict rational trajectory because of imbalances between sectors, side effects and coalition features. This means that 'weak sectors' may either accept decision premises from other sectors or engage in coalitions with them to get large projects decided on. The broader actors are able to anchor such large projects, i.e. the more different interests they can fulfil, the larger probability of reaching a decision on them. Such a pragmatic approach may be both crucial in realizing the projects at all and also move the projects away from the original ideas behind them.